Relapse detection in the Danish surveillance program of patients with clinical stage I seminoma: a nationwide study - Niklas B. Lindahl; Jakob Lauritsen; Thomas Wagner; Gedske Daugaard; Mikkel Bandak (Acta Oncologica)
Background and purpose: Active surveillance is a recommended management strategy for patients with clinical stage I (CSI) seminoma. This study aims to identify patterns of relapse detection methods in an unselected population-based cohort of CSI patients and provide evidence for a risk-adapted follow-up program.